Transformation of the Indonesian Education System through Strengthening Education Management, ICT, Quality, and Character Education - Rita Nurhayati; S Martono; Dwi Cahyaningdyah (Jurnal Visionary : Penelitian dan Pengembangan dibidang Administrasi Pendidikan, 2026)
Indonesia’s education system has undergone a long historical evolution, beginning with the colonial era, progressing through nationalization after independence, and continuing into the digital age. In the 21st century, global demands have encouraged substantial reforms in educational management, ICT integration, curriculum development, and the revitalization of national philosophical values. This article presents a comprehensive review of national academic publications (2021–2025) to map developments, challenges, and reform directions within Indonesia’s education system. Findings indicate that the major obstacles include weak school management, digital inequality, low teacher competencies, uneven access to education, and insufficient integration of philosophical foundations into educational practice. Conversely, opportunities for improvement arise from the expansion of ICT-based management systems, the modernization of school governance, the strengthening of character education, and the adoption of progressive educational principles. The study concludes that Indonesia’s educational transformation requires a synergistic approach combining managerial reform, technological advancement, philosophical grounding, and increased educator competence. Keywords: Transformation of Indonesian education, educational management, ICT, quality, character education. Abstrak: Sistem pendidikan Indonesia berkembang melalui proses historis panjang, mulai dari pengaruh kolonial, nasionalisasi pendidikan, hingga era digital saat ini. Memasuki abad ke-21, tuntutan global mendorong transformasi besar dalam manajemen pendidikan, integrasi ICT, pembaruan kurikulum, serta revitalisasi nilai-nilai filosofis nasional. Artikel ini menyajikan kajian komprehensif terhadap artikel ilmiah nasional (2021–2024) untuk memetakan perkembangan, permasalahan, dan arah pembenahan sistem pendidikan Indonesia. Analisis menemukan bahwa tantangan terbesar mencakup rendahnya kualitas manajemen sekolah, kesenjangan digital, lemahnya kualitas guru, ketidakmerataan pendidikan, dan kurangnya integrasi filosofi pendidikan dalam praksis pendidikan. Di sisi lain, peluang penguatan pendidikan muncul dari pemanfaatan ICT, manajemen modern, penguatan pendidikan karakter, pengembangan sistem informasi manajemen, serta penerapan prinsip progresivisme dalam pendidikan. Artikel ini menyimpulkan bahwa transformasi pendidikan Indonesia hanya dapat terjadi melalui sinergi antara pembaruan manajerial, teknologi, filosofi nasional, dan penguatan kompetensi pendidikan. Rekomendasi diarahkan pada penguatan tata kelola sekolah, investasi digital, perbaikan distribusi guru, dan reformasi kurikulum berbasis karakter dan teknologi. Kata kunci: Transformasi pendidikan Indonesia, manajemen pendidikan, ICT, mutu, pendidikan karakter.